Applied anatomy of the layers and soft tissues of the forehead during minimally‐invasive aesthetic procedures. (10th June 2022) - Bravo, Bruna Souza Felix; de Melo Carvalho, Raquel; Penedo, Lais; de Bastos, Julien Totti; Calomeni Elias, Mariana; Cotofana, Sebastian; Frank, Konstantin; Moellhoff, Nicholas; Freitag, Lysander; Alfertshofer, Michael
Abstract: Background: An increasing demand of minimally‐invasive aesthetic procedures of the forehead concomitantly leads to higher numbers of adverse events. Adequate application of anatomical knowledge is required to increase safety and efficacy of different minimally‐invasive aesthetic procedures in this anatomical region. Objective: To describe the layered anatomy of the forehead soft tissues with respect to their thicknesses and how they relate to different minimally‐invasive aesthetic treatments. Methods: A total of n  = 85 healthy study participants (69 females and 16 males) with a mean age of 40.84 ± 10.9 years and a mean body mass index of 22.65 ± 2.6 kg/m 2 were investigated with ultrasound‐based imaging to measure the thickness of different forehead soft tissues. Results: The mean overall soft tissue thickness of the forehead was measured to be 4.18 ± 0.7 mm for the entire study population. Increasing BMI values correlated statistically significantly with increasing thickness of all measured forehead soft tissues with exception of the frontalis muscle. On a statistically significant level, males showed thicker forehead soft tissues than females, with exception of the retrofrontalis fat and the frontalis muscle. Conclusion: On basis of the findings obtained in this study, basic treatment principles can be derived and improved for the injection of neuromodulators, hyaluronic acid as well as the application of polydiaxonane (PDO) threads and micro‐focused ultrasound. Precise knowledge and thorough understanding of the layers and soft tissues of the forehead is required to guarantee safe and effective procedures in this aesthetically important facial region.